THE PHENOMENON OF AUDIT REPORT LAG IN GO PUBLIC STATE OWNED COMPANIES: THE PHENOMENON OF AUDIT REPORT LAG IN GO PUBLIC STATE OWNED COMPANIES - DIna Amalis (International Journal of Management and Business (IJMB), 2023)
This study aims to find out how the phenomenon of Audit Report Lag that occurs in state-owned companies listed on the Indonesia Stock Exchange in 2013-2017. This type of research is descriptive explanatory research. The population in this study were all companies with the status of BUMN on the Indonesia Stock Exchange with a sample of 16 companies. The data used in this study is data on state-owned companies listed on the Indonesia Stock Exchange in 2013-2017. Based on the results of this study, the authors suggest that companies should pay attention to the audit report lag reporting period so that they are not subject to sanctions and violate the regulations set by BAPEPAM for delays. For investors, before making a decision to invest not only rely on data regarding changes in the company's stock price, but also need to pay attention to other factors related to the timeliness of submitting the company's financial statements to BAPEPAM and the completeness of the elements of the financial statements in it.